Andhracoides shabuddin gen. nov., sp. nov., a new phreatoicidean isopod (Crustacea, Hypsimetopidae) from hypogean aquatic habitats in Andhra Pradesh, India - Wilson, George D. F.; Reddy, Yenumula Ranga (Zootaxa, 2011)
A decade-long survey of ground waters in the state of Andhra Pradesh, India, has so far yielded over sixty new crustacean taxa, belonging to Copepoda, Bathynellacea, Amphipoda, Isopoda, and Ostracoda. This paper describes a new genus and species attributable to the phreatoicidean isopod family Hypsimetopidae Nicholls, and provides ecological and behavioural observations. The new taxon was found in Guthikonda Cave, which is about 8 km from Piduguralla town in the Palnadu area of Andhra Pradesh State. The species belonging to this clade are unusual in that their dorsoventrally flattened pleotelson gives them a non-phreatoicidean appearance. Because the postanal margin is missing, as in other members of the Hypsimetopidae, this is a superficial similarity rather than homology with other isopods. Other unusual features include robust blunt denticles on opposing margins of the pleotelson and protopod of the uropods. The species in this clade, of which Andhracoides shabuddin gen. nov., sp. nov. is only the first to be described, are related to Nichollsia Chopra & Tiwari, found in northeastern India, and to Pilbarophreatoicus Knott & Halse from the Pilbara region of Western Australia. The new species differs from its undescribed congeners in being nearly devoid of dorsal setae; other species of Andhracoides gen. nov. are much more hirsute.